Regional myocardial functional patterns: Quantitative tagged magnetic resonance imaging in an adult population free of cardiovascular risk factors: The multi‐ethnic study of atherosclerosis (MESA). Issue 1 (15th September 2014) - Venkatesh, Bharath Ambale; Donekal, Sirisha; Yoneyama, Kihei; Wu, Colin; Fernandes, Verônica R.S.; Rosen, Boaz D.; Shehata, Monda L.; McClelland, Robyn; Bluemke, David A.; Lima, João A.C.
<x xml:space="preserve">Abstract</x> Purpose To characterize the left ventricular (LV) regional deformation patterns and identify normal values of left ventricular strains from tagged magnetic resonance imaging (MRI) in a population with low‐risk‐factor (LRF) exposure. Materials and Methods Tagged CMR on three LV short axis slices was performed in participants of the MESA study who were free of cardiovascular disease at baseline. Images were analyzed by the harmonic phase imaging method to obtain: peak torsion, circumferential (Ecc) and radial (Err) strains, and systolic (SRs) and early‐diastolic (SRe) strain rates. An LRF group was created from the overall population based on strict exclusion criteria (n = 129) based on risk factors and events observed over a 10‐year follow‐up. Results The normative prediction intervals for the averaged peak Ecc (%) and torsion (deg/cm) measures were: in 45–59‐year‐old women: (–20.8, –13.2) and (2.1, 6.3); 60–84‐year‐old women: (–20.6, –12.8) and (2.2, 6.9); 45–59‐year‐old men: (–21.3, –13.5) and (1.9, 5.7); 60–84‐year‐old men: (–20.5, –12.5) and (1.5, 5.2). In general, African‐Americans (Ecc = –15.9, torsion = 3.3) had lower strains as compared to Chinese (Ecc = –17.1, torsion = 3.9), while Caucasians and Hispanics were intermediate and not significantly different. Circumferential shortening increased spatially from the epicardium to the endocardium (–16.9 to –18.2 at the mid‐ventricle) and from the base to the apex (–15.1 to –17.5 at the midwall). Conclusion The present study provides reference ranges and deformation patterns of deformation values from a large healthy population free of cardiovascular disease at baseline. J. Magn. Reson. Imaging 2015;42:153–159. © 2014 Wiley Periodicals, Inc.